Tinjauan Yuridis terhadap Tindak Pidana Akibat Penyalahgunaan Narkotika Ditinjau Menurut Hukum Positif Indonesia - Rasji; Arya Salwa (Jurnal Hukum Lex Generalis, 2024)
Narcotics abuse is a serious issue that has far-reaching impacts on public health, social well-being, and security. Indonesia has regulated narcotics-related crimes through Law Number 35 of 2009 on Narcotics, which includes the categorization of unlawful actions based on the type of narcotics and their severity, as well as strict criminal sanctions. Furthermore, the rehabilitative approach for users considered victims of addiction acknowledges that narcotics abuse is also a public health issue. This study employs normative legal research methods. Furthermore, judges are authorized to deliver rulings based on the facts of the case while considering the principles of justice, utility, and legal certainty. A judge's discretion in making decisions is constrained by legal provisions, Pancasila values, and social norms. An effective approach to narcotics eradication requires a comprehensive policy encompassing preventive, repressive, and rehabilitative aspects. With an integrated approach, it is hoped that a society free from the dangers of narcotics and healthier both physically and socially can be achieved.